2016
DOI: 10.1002/cne.24100
|View full text |Cite
|
Sign up to set email alerts
|

Cellular distribution of the fragile X mental retardation protein in the mouse brain

Abstract: The fragile X mental retardation protein (FMRP) plays an important role in normal brain development. Absence of FMRP, caused by transcriptional silencing of FMR1 gene, results in abnormal neuronal morphologies in a selected manner throughout the brain and leads to intellectual deficits and sensory dysfunction in the fragile X syndrome (FXS). Despite the paramount importance of FMRP for proper brain function, its overall expression pattern in the mammalian brain at the resolution of individual neuronal cell gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 90 publications
(128 reference statements)
5
53
1
Order By: Relevance
“…Recent cellular analyses, however, reported strong expression of FMRP in auditory brainstem cell groups across a number of vertebrate species . Quantitative analyses across the entire adult (5‐6 weeks) mouse brain further confirmed that auditory neurons in the brainstem and thalamus have levels of FMRP immunoreactivity comparable to those in cortical neurons . It is worth noting that FMRP is also expressed in spiral ganglion neurons, which convey acoustic signals from the inner ear to the brainstem, in both birds and mammals.…”
Section: Fmrp Regulates the Development Of Synaptic Transmission In Tmentioning
confidence: 86%
See 3 more Smart Citations
“…Recent cellular analyses, however, reported strong expression of FMRP in auditory brainstem cell groups across a number of vertebrate species . Quantitative analyses across the entire adult (5‐6 weeks) mouse brain further confirmed that auditory neurons in the brainstem and thalamus have levels of FMRP immunoreactivity comparable to those in cortical neurons . It is worth noting that FMRP is also expressed in spiral ganglion neurons, which convey acoustic signals from the inner ear to the brainstem, in both birds and mammals.…”
Section: Fmrp Regulates the Development Of Synaptic Transmission In Tmentioning
confidence: 86%
“…It is worth noting that FMRP is also expressed in spiral ganglion neurons, which convey acoustic signals from the inner ear to the brainstem, in both birds and mammals. In contrast, many cell groups in the midbrain and hypothalamus exhibit low FMRP levels …”
Section: Fmrp Regulates the Development Of Synaptic Transmission In Tmentioning
confidence: 95%
See 2 more Smart Citations
“…This pattern of results suggests that loss of FMRP leads to variable outcomes on white matter circuitry, consistent with evidence that the protein is expressed differentially across brain regions and over time 39 and is pronounced in subcortical sensory and motor cells. 40 …”
Section: Discussionmentioning
confidence: 99%